The Effect of Rotator Cuff Injury Rehabilitation Program according to Anthropometric Measurements in Volleyball Players from Sulaymaniyah Governorate - Saleh, Alan Salah; Ali, Zainab Abid (Journal of Physical Education, 2021)
The researchers aimed at designing a rehabilitation program using stretching exercises and proprioceptive neuromuscular facilitation (PNF). The researchers used the experimental methods on (9) young volleyball players to conclude that stretching exercises have a good effect on PNF rehabilitation in rotator cuff injury according to the anthropometric measurement for volleyball players as well as stretching exercises that develop proprioceptive neuromuscular facilitation (PNF) have a positive effect on rehabilitating rotator cuff injury in muscle, tendons according to anthropometric measurement.